The effect of age and gender on financial risk tolerance of South African investors - Zandri Dickason; Sune J. Ferreira (Investment Management & Financial Innovations, 2018)
Financial risk tolerance refers to the amount of risk a person is willing to take when making financial decisions. Previous researchers have found that demographic factors when used as independent variables to have an effect on the risk tolerance behavior of investors. Within this study, emphasis was given to gender and age within a sample of South African investors. Not much research on risk tolerance and demographics has been done in South Africa. Hence, an opportunity for further research within this field emerged. This study aimed to contribute towards the accurate risk profiling of South African investors based on their level of risk tolerance considering their gender and age. This study can be used as a future forecasting tool for investment companies to predict risk tolerance levels based on gender and age levels. Results from this study correspond to previous studies where male investors are more risk tolerant than female investors. A statistical difference was also found between male and female investors within the age categories of 35-49 years and investors older than 50 years. All age categories were found to be more risk tolerant for investors older than 50 years based on the binary regression.